CONTRIBUTING FACTORS AND INTERVENTION EFFORTS FOR DIABETES MELLITUS AMONG ADOLESCENTS: A LITERATURE REVIEW - Wardhani, Mira Kusuma (Jurnal EDUNursing, 2025)
The rising prevalence of Type 2 Diabetes Mellitus (T2DM) among adolescents has become a significant global public health concern, including in Indonesia. This literature review aims to explore the key contributing factors and effective countermeasures in addressing adolescent diabetes. Drawing upon 35 peer-reviewed studies published between 2018 and 2024, the review identifies obesity, physical inactivity, unhealthy dietary habits, and genetic predisposition as the most prominent risk factors. Additionally, emerging contributors such as psychosocial stress and sleep disturbances are gaining attention in recent studies. The review also examines various preventive and control efforts, including school-based health programs, family involvement, digital health interventions, and national policies such as GERMAS. While many intervention strategies show promise, implementation gaps and lack of culturally adapted models remain challenges, particularly in low- and middle-income countries. Compared to previous studies, this review highlights a shift toward more holistic and biopsychosocial approaches to T2DM prevention in youth. It concludes that multifaceted interventions tailored to adolescents' specific sociocultural contexts are essential for effective and sustainable outcomes. Further research is needed to expand local evidence and evaluate long-term impacts of ongoing health programs.